Reasons for poor adherence to Antiretroviral Therapy (ART) by young female (15 -24 years) HIV/AIDS patients in Oshakati district - Ehiemua, Uyinmwen Rosemary Aigbovbiosa (Stellenbosch : Stellenbosch University, 2015)
Thesis (MPhil)--Stellenbosch University, 2014.